2023
DOI: 10.3390/molecules28083412
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Occurring Chalcones with Aggregation-Induced Emission Enhancement Characteristics

Abstract: In this paper, the natural chalcones: 2′-hydroxy-4,4′,6′-trimethoxychalcone (HCH), cardamonin (CA), xanthohumol (XN), isobavachalcone (IBC) and licochalcone A (LIC) are studied using spectroscopic techniques such as UV–vis, fluorescence spectroscopy, scanning electron microscopy (SEM) and single-crystal X-ray diffraction (XRD). For the first time, the spectroscopic and structural features of naturally occurring chalcones with varying numbers and positions of hydroxyl groups in rings A and B were investigated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Key types include pelargonidin, cyanidin, peonidin, delphinidin, malvidin, and petunidin [57]. Chalcones are a class of compounds that serve as precursors to flavonoids, including marene, phloretin, lycochalcone-A, isobachalcone, and xanthohumol [58,59]. Flavonols are a subgroup of flavonoids characterized by the 3-hydroxyflavone backbone, comprising quercetin, kaempferol, rutin, myricetin, isoquercetin, and isorhamnetin [60].…”
Section: Antioxidant Effects Of Flavonoids and B[a]p In The Livermentioning
confidence: 99%
“…Key types include pelargonidin, cyanidin, peonidin, delphinidin, malvidin, and petunidin [57]. Chalcones are a class of compounds that serve as precursors to flavonoids, including marene, phloretin, lycochalcone-A, isobachalcone, and xanthohumol [58,59]. Flavonols are a subgroup of flavonoids characterized by the 3-hydroxyflavone backbone, comprising quercetin, kaempferol, rutin, myricetin, isoquercetin, and isorhamnetin [60].…”
Section: Antioxidant Effects Of Flavonoids and B[a]p In The Livermentioning
confidence: 99%
“…Similarly, Lee and colleagues demonstrated the inhibitory effect of Lico-A on AChE activity in Tet-On Aβ-GFP 293/SH-SY5Y cells [ 15 ]. Budziak-Wieczorek and colleagues highlighted Lico-A’s neuroprotective properties, showcasing its antioxidant activity as well as its inhibition of both AChE and butyrylcholinesterase (BuChE) enzymes (AChE IC50 23.41 ± 0.02 µM, BuChE IC50 42.28 ± 0.06 µM) [ 14 ].…”
Section: Licochalcone A: a Natural Compound With A Multitarget Sidementioning
confidence: 99%
“…Licochalcone A (Lico-A) is a phenolic compound derived from the root extract of the Glycyrrhiza species that has demonstrated promising neuroprotective properties and therapeutic potential for AD [ 13 ]. Preclinical studies have reported the ability of Lico-A to reduce amyloid plaques and tau phosphorylation, exhibit anti-inflammatory and antioxidant effects, and inhibit acetylcholinesterase activity [ 14 , 15 , 16 ]. These multitarget actions suggest that Lico-A could have beneficial effects on key mechanisms implicated in AD pathogenesis.…”
Section: Introductionmentioning
confidence: 99%